The Effects of Conversion to Islam of a Non-Muslim Spouse on the Custody of Minor Children-Thoughts and Trends from a Malaysia Perspective - Nair, H.L.; Chuan, G.C. (American Scientific Publishers, 2017)
As a result of globalization and the fact that we are living in a pluralistic society, religious conversion from one faith to another may happen for many reasons; the most common being for the sake of marriage. However, when there is a breakdown in the marriage, as a consequence of the religious conversion of a spouse to another faith, which subsequently subjects the parties to different legal systems and jurisdiction, the issue in respect of custody of minor children can become problematic and complicated. In Malaysia, interfaith custody battle between a non-Muslim and a Muslim spouse has becomes a predominant issue in recent times. Separate legal systems and different jurisdiction governing the respective parties as a result of the religious conversion of a spouse to Islam, has made the issue of custody of minor children very challenging and distressing, not only for the respective parties, but the minor children who are torn between the parents. This paper aims to highlight to what extent the welfare and best interest of the child is considered by the Courts in awarding custody to the respective parents in an interfaith custody dispute by scrutinising past decided cases against the latest landmark decision by the Federal Court of Malaya in resolving this pertinent interfaith custody dispute amongst the parties.